The problem of complexity and Consistency in the intelligence cycle: A critique of the effects of structural and dynamic interactions on intelligence efficiency - Ibrahim, Mohamed Elzin Mohamed Ahmed (Arab Journal for Sciences and Research Publishing, 2024)
The study seeks to address the issue of complexity and consistency in the intelligence cycle, aiming to critique the impact of structural and dynamic interactions on intelligence efficiency, in light of technological advancements and changes in the threat environment. The study argues that the process of complexity within this cycle leads to challenges in the speed of information management, decision-making flexibility, and the responsiveness of intelligence systems. Therefore, the study aims to analyze the challenges associated with complexity and consistency in the intelligence cycle by exploring the effects of structural and dynamic interactions on the performance of intelligence agencies in the context of global transformations. Thus, the problem revolves around the central question: How do structural and dynamic interactions within the intelligence cycle affect its efficiency? The study aims to analyze these interactions and their effects on operational and intelligence effectiveness, focusing on the structural and dynamic strengths and weaknesses. The study is based on a central hypothesis: improving structural consistency and reducing dynamic complexity leads to enhanced intelligence operations efficiency. The research relies on historical methodology, analytical description, and critical approaches to understand the dimensions of these interactions. The study concludes with several findings, the most important of which are the need for technological integration and linking modern tools with the traditional intelligence system to ensure it performs its tasks efficiently. Furthermore, the precise management of interactions and the controlled use of technology enhances intelligence performance efficiency. The study recommends updating the intelligence cycle system to address the complexities of intelligence operations and developing integrated models that combine traditional intelligence cycles with modern technology, ensuring the integration of smart analysis tools with traditional information-gathering methods.